THEORETICAL ASPECTS OF FORECASTING ENERGY CLUSTER DEVELOPMENT TAKING INTO ACCOUNT OF MODERN INNOVATION- INVESTMENT TRENDS - Bondar, O.A.; Klymchuk, M.M.; Shovkivska, V.V.; Klochko, A.A.; Malik , R.Yu. (The actual problems of regional economy development, 2019)
The theoretical aspects of predicting the development of an energy cluster are investigated in the article, since the energy cluster itself should create conditions for basic, complex development within the objective function aimed at activating it technological, scientific, technical, industrial, commercial and human resources, as well as prejudice, minimization of active and passive economic threats related, for example, to fragmented state policy in the sphere of supporting the functioning of integration entities. The problems of formation of new models of organization of joint activity of enterprises, namely the energy cluster as one of the tools for creation of innovative high-tech economy and attraction of investments, have been updated. Grouping of approaches to economic and mathematical development of the energy cluster is carried out, which highlights the advantages and disadvantages of groups of models of innovative economic development in the form of a vector linear programming problem, models based on one or a group of criteria indicators or on the concept of balance, and based on the analysis of the structure of economic object. The organizational and economic system of elements of the energy cluster is provided, which ensures the stability of its operation, achievement of financial and commercial success, progressive scientific and technical and social development taking into account the current tendencies of the world economic, industrial and scientific transformations. The complex of factors of development of energy cluster and princes of adaptation are presented, the use of which will contribute to the effective solution of problems of rational use of energy resources within the framework of integration formation.